The effect of fuel area size on behavior of fires in a reduced-scale single-track railway tunnel. (February 2016) - Chen, Chang-kun; Zhu, Cong-xiang; Liu, Xuan-ya; Kang, Heng; Zeng, Jia-wei; Yang, Jian
Graphical abstract: Highlights: Small-scale experiment on tunnel fire behaviors of varied fuel areas was conducted. Temperature distribution in the tunnel and radiation near the entrance were tested. Characteristics of fuel burning, smoke stratification, jet flame, etc. were analyzed. Depressed burning near fire source occurs as fuel area enlarged to a certain value. Ceiling temperature of different fuel areas along tunnel was analyzed and compared. Abstract: A set of experiments was carried out in a 1/9 reduced-scale single-track railway tunnel to investigate the effect of fuel area size on the temperature distribution and behavior of fires in a tunnel with natural ventilation. Methanol pool fires with four different fuel areas 0.6 × 0.3 m 2 (1 pan), 1.2 × 0.3 m 2 (2 pans), 2.4 × 0.3 m 2 (4 pans) and 3.6 × 0.3 m 2 (6 pans), were used in these experiments. Data were collected on temperatures, radiative heat flux and mass loss rates. The temperature distribution and smoke layer in the tunnel, along with overflow dimensions and radiant heat at the tunnel entrance were analyzed. The results show that as the fuel area enlarges, the fire gradually becomes ventilation-controlled and the ceiling temperature over the center of fire source declines. Burning at the central region of fire source is depressed due to lack of oxygen. This makes the temperature distribution along the tunnel ceiling change from a typical inverted V-shape to an M-shape. As observed in the experiments, a jet flame appeared at tunnel entrances and both the size and temperature of the flame increased with the enlargement of fuel area leading to a great threat to firefighters and evacuees in actual tunnel fires.